Chemical exchange-sensitive spin-lock MRI of glucose analog 3-O-methyl-d-glucose in normal and ischemic brain. Issue 5 (May 2018) - Jin, Tao; Mehrens, Hunter; Wang, Ping; Kim, Seong-Gi
Glucose transport is important for understanding brain glucose metabolism. We studied glucose transport with a presumably non-toxic and non-metabolizable glucose analog, 3-O-methyl-d -glucose, using a chemical exchange-sensitive spin-lock MRI technique at 9.4 Tesla. 3-O-methyl-d -glucose showed comparable chemical exchange properties withd -glucose and 2-deoxy-d -glucose in phantoms, and higher and lower chemical exchange-sensitive spin-lock sensitivity than Glc and 2-deoxy-d -glucose in in vivo experiments, respectively. The changes of the spin-lattice relaxation rate in the rotating frame (Δ R 1 ρ) in normal rat brain peaked at ∼15 min after the intravenous injection of 1 g/kg 3-O-methyl-d -glucose and almost maintained a plateau for >1 h. Doses up to 4 g/kg 3-O-methyl-d -glucose were linearly correlated with Δ R 1 ρ. In rats with focal ischemic stroke, chemical exchange-sensitive spin-lock with 3-O-methyl-d -glucose injection at 1 h after stroke onset showed reduced Δ R 1 ρ in the ischemic core but higher Δ R 1 ρ in the peri-core region compared to normal tissue, which progressed into the ischemic core at 3 h after stroke onset. This suggests that the hyper-chemical exchange-sensitive spin-lock region observed at 1 h is the ischemic penumbra at-risk of infarct. In summary, 3-O-methyl-d -glucose-chemical exchange-sensitive spin-lock can be a sensitive MRI technique to probe the glucose transport in normal and ischemic brains.